Integrative molecular characterisation of gallbladder cancer reveals micro-environment-associated subtypes - Nepal, Chirag; Zhu, Bin; O’Rourke, Colm J.; Bhatt, Deepak Kumar; Lee, Donghyuk; Song, Lei; Wang, Difei; Van Dyke, Alison L.; Choo-Wosoba, Hyoyoung; Liu, Zhiwei; Hildesheim, Allan; Goldstein, Alisa M.; et al. (Journal of hepatology, 2021)
Background & Aims - Gallbladder cancer (GBC) is the most common type of biliary tract cancer, but the molecular mechanisms involved in gallbladder carcinogenesis remain poorly understood. In this study, we applied integrative genomics approaches to characterise GBC and explore molecular subtypes associated with patient survival. - Methods - We profiled the mutational landscape of GBC tumours (whole-exome sequencing on 92, targeted sequencing on 98, in total 190 patients). In a subset (n = 45), we interrogated the matched transcriptomes, DNA methylomes, and somatic copy number alterations. We explored molecular subtypes identified through clustering tumours by genes whose expression was associated with survival in 47 tumours and validated subtypes on 34 publicly available GBC cases. - Results - Exome analysis revealed TP53 was the most mutated gene. The overall mutation rate was low (median 0.82 Mut/Mb). APOBEC-mediated mutational signatures were more common in tumours with higher mutational burden. Aflatoxin-related signatures tended to be highly clonal (present in ≥50% of cancer cells). Transcriptome-wide survival association analysis revealed a 95-gene signature that stratified all GBC patients into 3 subtypes that suggested an association with overall survival post-resection. The 2 poor-survival subtypes were associated with adverse clinicopathologic features (advanced stage, pN1, pM1), immunosuppressive micro-environments (myeloid-derived suppressor cell accumulation, extensive desmoplasia, hypoxia) and T cell dysfunction, whereas the good-survival subtype showed the opposite features. - Conclusion - These data suggest that the tumour micro-environment and immune profiles could play an important role in gallbladder carcinogenesis and should be evaluated in future clinical studies, along with mutational profiles. - Lay summary - Gallbladder cancer is highly fatal, and its causes are poorly understood. We evaluated gallbladder tumours to see if there were differences between tumours in genetic information such as DNA and RNA. We found evidence of aflatoxin exposure in these tumours, and immune cells surrounding the tumours were associated with survival.